PENDUDUK KOTA LAPAR LAHAN PERMUKIMAN (KASUS DI KOTA SEMARANG) - Hariyanto, Hariyanto (Forum Ilmu Sosial, 2012)
Safety factor ought to become consideration ‘first and principle’ in settlement preferensi; because some reason, the factor often neglectful. Growth of fast setlement in town, forced or voluntary of people live in sensitive land slide area. How danger attitude them slide, and how their anticipation is the purpose of this research. The method are analysis aliance survey field cheque and survey in society. Research location selected pursuant to crisis storey, level slide in setlement area. Survey Family Head sampel ( KK) who live in sensitive land slide area by random counted 100 housing. Result of research, indicating that anticipatory model which developed by still have the character of eye physical (technique engineering and reforestation), not yet touched education in society, training of disaster, etc. Anticipatory model slide is influenced by structure of economy land wide, and status of occupation. Anticipation imigrant housing with technique engineering; while aborigin with reforestation. To face disaster, society still have individual character, not yet collectively. The interesting one are they who live in sensitive land slide area not only poor people wich has no alternative, but also rich people wich have many choice.